Inductive power system for energy harvesting - Arshad, Atika; Tasnim, Rumana; Khan, Sheroz; Alam, A. H. M. Zahirul (IIUM Press, 2011)
Inductive sensor systems have been becoming topics of heated debate among researchers for applications of industrial automation and biomedical applications because of its oonliCllcss means of transferring energy and also due to lhe high demand of low power and low vohage integrated circuit devices. These devices arc enabling light wcight dcsigns for applications such as in movement and displacement measurement. temperature, hlood pressure, hean rale devices, wireless capsule endoscopy, and power transfer across narrow gaps